A New Regularity Criterion for the Three-Dimensional Incompressible Magnetohydrodynamic Equations in the Besov Spaces. (29th August 2021) - LI, TianLi; Wang, Wen; Liu, Lei
Abstract : Regularity criteria of the weak solutions to the three-dimensional (3D) incompressible magnetohydrodynamic (MHD) equations are discussed. Our results imply that the scalar pressure field π plays an important role in the regularity problem of MHD equations. We derive that the weak solution u, b is regular on 0, T, which is provided for the scalar pressure field π in the Besov spaces.